GAMBARAN TINGKAT PENGETAHUAN REMAJA TENTANG PERNIKAHAN DINI DI SMK NEGERI 5 DENPASAR - Amalia, A'isyah Agustina; Pramitaresthi, I Gusti Ayu; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p05, 2023)
Early marriage is a phenomenon that becomes a serious problem in the current era of globalization both in Indonesia and abroad. Based on PUSKAPA data in 2020, 1.220.900 women in Indonesia were married under the age of 18. This causes Indonesia to be in the top 10 with cases of early marriage in the world. One of the reasons of this phenomenon is the lack of knowledge of teenagers due to the fact that the provision of knowledge related to sex and early marriage is still considered taboo by the family. This study aimed to describe the level of teenegers knowledge of early marriage at SMK Negeri 5 (State Vocational High School) Denpasar. This research is a quantitative descriptive study with cross sectional approach. The sample in this study was taken at SMK Negeri 5 Denpasar, students of class X majoring in UPW using a simple random sampling technique, and the sample is 83 students. Data collection used a questionnaire on adolescent knowledge about early marriage, which was adapted from previous research. Univariate data analysis was used in the study. Data is presented in the form of central tendency and frequency distribution. Based on the results of the study, it was found that the majority of students were 16 years old and female (57,8%). Then the results obtained showed that students have a level of knowledge about early marriage as follows: good category (50,6%), sufficient category (38,6%), and bad category (10,8%). However, some items still unknown by respondents, which are marked by the dominance of wrong answers on several question items so that providing information related to knowledge about early marriage remains important.